Exenatide extended-release: a once weekly treatment for patients with type 2 diabetes - Mann, Katherine V (Dove Medical Press, 2014)
BACKGROUND: This article reviews the clinical efficacy, safety, and patient outcomes literature on the first once weekly treatment for type 2 diabetes mellitus (T2DM), exenatide extended-release (ER). METHODS: Relevant literature on exenatide ER and T2DM was identified through PubMed database searches from inception until April 2014. RESULTS: Exenatide ER is the first medication for the treatment of T2DM dosed on a weekly schedule. Exenatide ER is a glucagon-like peptide-1 (GLP-1) receptor agonist, the third to be approved in the US, and is associated with a low risk of hypoglycemia, may result in weight loss, and has proven to be a safe and effective treatment for T2DM. Exenatide ER reduces A(1c) levels by decreasing fasting and postprandial hyperglycemia. The most common adverse events are gastrointestinal in nature, which are lesser in frequency than those observed with short-acting exenatide. Exenatide ER has been shown to be more effective than exenatide twice daily and slightly less efficacious than liraglutide. Exenatide ER is useful as monotherapy and in combination with other oral antidiabetic drugs. CONCLUSION: Once weekly treatment options for diabetes such as exenatide ER have the potential to offer substantial convenience for patients who have high medication burden and poor medication adherence.